Experimentando la evaluación continua en un curso de Matemática dirigido a estudiantes de las carreras de Humanidades - Advíncula, Elizabeth Milagros (2013)
The aim of this article is to introduce an experience in continuous evaluation applied to a course of Mathematics taken by students pursuing a career in the Humanities; in other words, students that won’t use Mathematics in their future professions. Even though the concept of continuous evaluation is not often heard in higher education, we decided to incorporate this evaluation system in our course as we think it may have a positive impact on the students’ learning process –specially of those pursuing a career in the Humanities. As this kind of evaluation is a continuous and interactive process, it stimulates the development of mathematical skills, and allows students to succeed when facing problems related to every-day life or to their employments.